Learning from the global economic crisis. - Paderanga, C.
The world nees an international monetary system that promotes global price stability, facilitates world economic growth, and ensures global financial stability. Global crises provide rare opportunities in reforming the international monetary system. The ability to provide adequate liquidity, timely and adequate adjustment of imbalances, and reduced risk has proven to be elusive under the current system centered on the US dollar. The stability of the global economic system, in effect, hinges on the United States being the deficit country of last resort. There is a need for fundamental reforms in the current dollar-centric system. This paper presents proposals for reformation of the international monetary system.